Analisis Penyaluran Dana Infak dalam Perkembangan Usaha dan Peningkatan Keuntungan Penerima Infak (Studi di Baitul Mal Banda Aceh) - Rina Desiana; Awang Darmawan Putra; Muhammad Kausar (Maqrizi: Journal of Economics and Islamic Economics, 2022)
The development of infaq funds is productive by using it as business capital to empower the community's economy. With infaq funds allocated for the poor, they will get a steady income, increase their business, and develop their business so that they can live a more decent life. Increasing profits is the ultimate goal of successful businesses carried out by the community, the level of profit can be used as a measure of the success of businesses receiving business capital assistance. With the increase in profits, business actors can develop their business, develop quality, better service, increase the amount of production, and can expand business branches and add employees. The purpose of this study is to analyze the distribution of infaq funds in business development and increase the profits of infaq recipients. This research is a descriptive-based research with a qualitative approach, the data used in this study are primary data and secondary data. The results of this study are the distribution of infaq funds as business capital to provide business development and increase the profits of recipients of infaq funds as business capital.